الدرس الصوتي بين الخليل بن أحمد الفراهيدي وفخر الدين الرازي " دراسة مقارنة - أحلام زعبي; حياة سعدون (University of Eloued جامعة الوادي, 2025)
لقد تعرفنا في بحثنا هذا على أهمية علم الأصوات، فهو محور أساسي في علوم اللغة العربية عبر العصور، كما تطرقنا إلى الدرس الصوتي عند العلماء القدامى بأخذ الخليل بن أحمد الفراهيدي وفخر الدين الرازي نموذجا ، وتعرفنا على مفهوم الصوت عند كليهما، ومخارج الحروف وصفاتها، وبعدهما الفنونولوجي، حيث أثبت كل من الفراهيدي والرازي أن الصوت هو أساس اللغة ومفتاح فهم بنيتها الصحيحة، وأن العناية به ضرورية لصيانة اللسان العربي وفهم النصوص وترسيخ الهوية اللغوية. كما تعرفنا أن للخليل الريادة والأسبقية العلمية: فهو يُعد الرائد المؤسِّس لعلم الأصوات العربي؛ إذ وضع أوّل نظرية متكاملة لمخارج الحروف وصفاتها وترتيبها، ووصف الظواهر الصوتية في العربية بعبقرية منهجية سبقت زمنه، وظلت مبادئه الصوتية صالحة ومعتبرة حتى مع تطور العلوم الحديثة، كما تبيّن أنه رغم مجال فخر الدين الرازي المغاير، أنه قدّم إسهامًا معتبرًا في علم الأصوات، خاصة في مجال التأصيل النظري لمفهوم الصوت والحرف والحركة، ويظهر هذا جليا في تفسيره للقرآن الكريم . وفي الختام توصلنا إلى أنه رغم اختلاف المنطلقات (الاستقراء اللغوي عند الخليل والاستدلال المنطقي عند الرازي)، ورغم اختلاف المناهج (منهج الخليل الوصفي التجريبي ومنهج الرازي التحليلي العقلي) توصلا في النهاية إلى نتائج متقاربة في الجوهر حول طبيعة الأصوات ووظائفها. Abstract : In our research, we explored the importance of phonetics, which is a fundamental pillar in Arabic linguistic sciences throughout the ages. We also addressed the study of phonetics among early scholars, focusing on Al-Khalil ibn Ahmad Al-Farahidi and Fakhr al-Din Al-Razi as examples. We examined their understanding of sound, the articulation points and characteristics of letters, and later the phonological aspects. Both Al-Farahidi and Al-Razi demonstrated that sound is the foundation of language and the key to understanding its correct structure. They also emphasized that attention to phonetics is essential for preserving the Arabic tongue, comprehending texts, and strengthening linguistic identity. **We also discovered that Al-Khalil holds the pioneering and foundational position in Arabic phonetics. He is considered the founding father of this science, as he developed the first comprehensive theory of articulation points, letter characteristics, and their order. He described Arabic phonetic phenomena with a methodological genius ahead of his time. His phonetic principles have remained valid and respected even with the advancement of modern sciences. Despite Fakhr al-Din Al-Razi working in a different field, he made significant contributions to phonetics, particularly in the theoretical conceptualization of sound, letters, and vowels. This is especially evident in his interpretation of the Holy Qur’an. *In conclusion, we found that despite their differing starting points (Al-Khalil’s linguistic induction versus Al-Razi’s logical reasoning) and their differing methodologies (Al-Khalil’s descriptive-empirical method versus Al-Razi’s analytical-logical approach), they ultimately arrived at similar core conclusions regarding the nature and functions of sounds. ‎
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: Phonetic study – Al-Khalil – Al-Razi; الدرس الصوتي- عند خليل-الرازي